(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
Drawing on the work of Jean-Paul Sartre, this paper develops an existential approach to sex and sexuality. The initial focus draws on Sartre’s early work pertaining to ’being for others’, before considering the significance of his later work, in particular his attempts to contextualise the individual within a social and historical context.